English for Children with Special Needs: Obstacles and Solutions in the Teaching and Learning Process - Akhmad Feri Fatoni; Sri Yunita Suraida Salat; Iva Gamar Dian Pratiwi (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
English is taught in primary education classes, including for students with special needs. Students with special needs certainly need treatment that is not the same as students in general. This study aims to determine the obstacles experienced by students with special needs in learning English, as well as solutions made by teachers. This research used a mixed method, a combination of qualitative and quantitative. Qualitative data were obtained from conducting in-depth interviews with teaching teachers to discover the obstacles and solutions in the teaching and learning process of English subjects. In contrast, quantitative data were obtained from test results to determine the significance of solutions for each disability. Based on the data from the in-depth interview, researchers formulated that there were various obstacles in the learning process. The main factor of these obstacles is the limitations experienced by students. Teachers use the learning media "YouTube" to solve these obstacles. Quantitative test data showed that there were significant differences between blind and autistic (0.003), deaf and autistic (0.00), quadriplegic and autistic (0.00), deaf and intellectual disabilities (0.02), and quadriplegic and intellectual disabilities (0.01). Based on the results of the data above, the researchers concluded that the obstacles faced by ABK students vary and depend on the limitations of each disability. There are significant differences in learning outcomes between blind, quadriplegic, and deaf students when compared to intellectual disabilities and autistic students in learning English using the "YouTube" platform.